Mutational Spectrum of the C1 Inhibitor Gene in a Cohort of Italian Patients with Hereditary Angioedema: Description of Nine Novel Mutations. (24th January 2014) - Bafunno, Valeria; Bova, Maria; Loffredo, Stefania; Divella, Chiara; Petraroli, Angelica; Marone, Gianni; Montinaro, Vincenzo; Margaglione, Maurizio; Triggiani, Massimo
Summary: Hereditary angioedema (HAE) is an autosomal dominant disease due to mutations in the C1 inhibitor gene ( C1NH ) that affects protein synthesis (HAE type I) or function (HAE type II). In 45 subjects affected by HAE diagnosed through clinical features and C1 inhibitor deficiency from the south of Italy (38 with type I and 7 with type II HAE), the whole C1NH coding region was screened for mutations by direct DNA sequencing. A severity score based on clinical manifestation, age at disease onset, and need for long‐term prophylaxis was used to investigate possible genotype‐phenotype correlations. A series of 22 different mutations was identified: nine missense (40.9%), five nonsense (22.7%), six frameshift (27.3), one small deletion (4.5%), and one splicing defect (4.5%). Nine C1NH mutations have not been previously described. No correlation was found between C1 inhibitor function level and severity score or age at first attack. Moreover, there was no correlation between different types of mutations and clinical phenotype. The number of different mutations identified highlights the heterogeneity of C1 inhibitor deficiency and supports the hypothesis that HAE clinical phenotype is not strictly related to the type of mutation but rather depends on unknown factors.